MENINGKATKAN KEMAMPUAN MENGENAL KONSEP ANGKA MELALUI MEDIA KOTAK ANGKA BAGI ANAK BERKESULITAN BELAJAR - Ikang Patrizal, Damri, Irdamurni (Universitas Negeri Padang, 2013)
This study begins with a young child encountered learning disabilities who are not familiar with the concept of numbers. From my observation, children do not know the shape of the 1 - 10. Research aims to improve the ability to know the concept of numbers in children learning disabilities through media box numbers. This study uses ABA design in the form of Single Subject Research (SSR). Results of this study showed the box number media can improve the ability to know the concept of numbers for children first grade learning disabilities in SDN. 18 Koto Luar Padang.